Evaluación del desempeño laboral al personal docente y administrativo de la Escuela de Educación Básica Particular “San Francisco Javier”, con la herramienta de 360 grados periodo lectivo 2021-2022 - Carrillo Cando, Dennise María (2023)
It is the degree of competitiveness that currently exists worldwide, which makes educational institutions compete every day to be the best, that is why a proposal for job performance evaluation was done to the teaching and administrative staff of "San Francisco Javier" Private School, with the 360 degree tool. It was a descriptive investigation with a mixed approach, 16 teachers and 4 administrators participated as the study population, the evaluation method used was 360 degrees where students and parents, clients of the institution, also participated in the evaluation. As a first point, the teaching and administrative staff were done aware of the 360- degree evaluation. Consequently, once the evaluation was carried out by the workers, the data collection and processing were carried out where a Likert scale was adopted to measure the indicators of management, skills and abilities, where the results have gotten and showed that the relationship with the community by the teachers of the institution is not being fully fulfilled, obtaining a score of 2.85 equivalent to 57%. Once the evaluation was completed, the results were delivered personally to the director, so that she informed each of the workers in a confidential manner, so that later the feedback process was given in order to promote a positive difference in Performance. Finally, an improvement proposal was raised which allowed the development of those weaknesses detected in the 360-degree evaluation.